A Human‐Specific De Novo Gene Promotes Cortical Expansion and Folding. Issue 7 (13th January 2023) - Qi, Jianhuan; Mo, Fan; An, Ni A.; Mi, Tingwei; Wang, Jiaxin; Qi, Jun‐Tian; Li, Xiangshang; Zhang, Boya; Xia, Longkuo; Lu, Yingfei; Sun, Gaoying; Wang, Xinyue; et al.
Abstract: Newly originated de novo genes have been linked to the formation and function of the human brain. However, how a specific gene originates from ancestral noncoding DNAs and becomes involved in the preexisting network for functional outcomes remains elusive. Here, a human‐specific de novo gene, SP0535, is identified that is preferentially expressed in the ventricular zone of the human fetal brain and plays an important role in cortical development and function. In human embryonic stem cell‐derived cortical organoids, knockout of SP0535  compromises their growth and neurogenesis. In SP0535  transgenic (TG) mice, expression of SP0535  induces fetal cortex expansion and sulci and gyri‐like structure formation. The progenitors and neurons in the SP0535  TG mouse cortex tend to proliferate and differentiate in ways that are unique to humans. SP0535  TG adult mice also exhibit improved cognitive ability and working memory. Mechanistically, SP0535 interacts with the membrane protein Na + /K + ATPase subunit alpha‐1 (ATP1A1) and releases Src from the ATP1A1‐Src complex, allowing increased level of Src phosphorylation that promotes cell proliferation. Thus, SP0535  is the first proven human‐specific de novo gene that promotes cortical expansion and folding, and can function through incorporating into an existing conserved molecular network. Abstract : Herein, the first complete study of biological function of a human‐specific de novo protein in human cortical organoids and mice is reported. The de novo gene is potentially involved in cortical enlargement and folding during development and might participate in the acquisition of high intelligence.